2014
DOI: 10.1038/emm.2013.152
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-21 controls the development of osteoarthritis by targeting GDF-5 in chondrocytes

Abstract: Osteoarthritis is a common cause of functional deterioration in older adults and is an immense burden on the aging population. Altered chondrogenesis is the most important pathophysiological process involved in the development of osteoarthritis. However, the molecular mechanism underlying the regulation of chondrogenesis in patients with osteoarthritis requires further elucidation, particularly with respect to the role of microRNAs. MiR-21 expression in cartilage specimens was examined in 10 patients with knee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
72
1
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(78 citation statements)
references
References 28 publications
3
72
1
2
Order By: Relevance
“…Three independent experiments were performed in each assay. Several studies had demonstrated that miRNAs played a vital role in the regulation of the OA development, including miR-210 (21), miR-16 (22), miR-21 (23), and miR-142 (24). This study found the up-regulation of miR-4262 in TNF-α-treated chondrocytes.…”
Section: Discussionsupporting
confidence: 58%
“…Three independent experiments were performed in each assay. Several studies had demonstrated that miRNAs played a vital role in the regulation of the OA development, including miR-210 (21), miR-16 (22), miR-21 (23), and miR-142 (24). This study found the up-regulation of miR-4262 in TNF-α-treated chondrocytes.…”
Section: Discussionsupporting
confidence: 58%
“…The aberrant miRNA expression profiles have been demonstrated to be associated with OA [10,11], and miRNAs acted as important regulators in OA development, as well as participated in inflammatory response [12,13]. Previous studies have demonstrated that many miRNAs were involved in the regulation of OA, such as miR-320, miR-21, and miR-140 [14][15][16]. The miR-146a, as a negative regulator of leukocyte immune response, is involved in many other cell processes including cancer cell proliferation [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Overexpression of miR-21 was reported to promote chondrocyte proliferation and matrix synthesis; interestingly, miR-21 was found to be reduced by food restriction [48] and to target GDF-5 in chondrocytes [115]. In an osteoarthritis model, the introduction of miR-21 stimulated the apoptosis of chondrocytes and inhibited the expression levels of autophagic complexes, including LC-3B, supporting our observation of increased autophagy in response to food restriction.…”
Section: Local Molecular Mechanisms In Malnutrition and Cu Growthsupporting
confidence: 71%
“…Moreover, in our model of nutritionally induced CU growth, we found that in the CU group, in contrast to the RES group, there was a rapid significant increase in the serum level of GDF-5 [112], suggesting an additional link between nutrition (mediated by the adipose tissue) and longitudinal growth. GDF-5 is also a target for nutritionally induced microRNAs (miRNAs, see below) [115] indicating an important role in the nutrition–growth complex. …”
Section: Systemic Factors In Malnutrition and Cu Growthmentioning
confidence: 99%